2019
DOI: 10.3390/pharmaceutics11080399
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Skin Penetration, Antipollutant Activity and Skin Hydration of 7,3′,4′-Trihydroxyisoflavone Cyclodextrin Inclusion Complex

Abstract: As is known, many antioxidants from plant extracts have been used as additives in skincare products to prevent skin damage following overexposure to environmental pollutants. 7,3′,4′-trihydroxyisoflavone (734THIF), an isoflavone compound, possesses various biological activities, including antioxidant, antityrosinase, photodamage protection, and anticancer effects. Unfortunately, 734THIF has poor water solubility, which limits its skin penetration and absorption, and subsequently influences its biological activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“… 29 Nanoparticle formulations could improve the water solubility of small-molecule compounds, such as hydrophobic flavonoids 30 and isoflavone. 31 In our study, PSN prepared using EE and PVA were shown to improve the water solubility and drug release of PTS by reducing the particle size, inducing an amorphous transformation, and leading to the formation of hydrogen bonds with nanocarriers. In addition, PSN had a better dissolution profile in PBS at pH 5.5 but not at pH 7.4.…”
Section: Discussionmentioning
confidence: 71%
“… 29 Nanoparticle formulations could improve the water solubility of small-molecule compounds, such as hydrophobic flavonoids 30 and isoflavone. 31 In our study, PSN prepared using EE and PVA were shown to improve the water solubility and drug release of PTS by reducing the particle size, inducing an amorphous transformation, and leading to the formation of hydrogen bonds with nanocarriers. In addition, PSN had a better dissolution profile in PBS at pH 5.5 but not at pH 7.4.…”
Section: Discussionmentioning
confidence: 71%
“…Indeed, PM induces the phosphorylation and nuclear translation of the p65 unit [128,130,136,137,145,169,179,181,231,233]. The PM-induced activation of NF-κB leads to the increased transcription of its target genes and their protein expressions such as IL-1α, IL-1β, IL-6, IL-8, ICAM1, COX2 and TNF-α [124,128,130,133,135,138,139,142,169,173,181,227,229,230,243]. PM-induced COX2 expression leads to induced production of PGE 2 [122,126,137,143,179,181,231,232].…”
Section: Pm-induced Activation Of Nf-κbmentioning
confidence: 99%
“…Niacinamide, a compound that is often used in various cosmetics, was shown to protect keratinocytes from PMinduced oxidative stress [184]. Other reducing agents found to protect the skin against PM are 3,4-dicaffeoylquinic acid [186], 7,3′,4′-trihydroxyisoflavone cyclodextrin inclusion complex [142], isovitexin [176], ginsenoside Rb1 [175], chitosan [259], and SIG-1273, a isoprenylcysteine small molecule [228].…”
Section: Protective Solutions Against Pm-induced Skin Damagementioning
confidence: 99%
“…Human keratinocyte HaCaT was from Prof. Yen, Kaohsiung Medical University ( Huang et al, 2019 ), and monocyte THP-1 cell line was obtained from Bioresource Collection and Research Center (BCRC). HaCaT and THP-1 cells were maintained in Dulbecco’s Modified Eagle Medium (DMEM) and RPMI 1640, respectively, supplemented with 10% fetal bovine serum (FBS) and 1% penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%